(untitled) (Agroindustria, Sociedad y Ambiente, 2020)
Confectionery is a branch of the food industry that is mainly characterized by the use of large amounts of additives and sugars with high caloric content, which when metabolized by consumers can generate a large number of degenerative diseases. Due to this problem, the present research sought to develop a new agroindustrial product without the addition of refined sugars, in order to help mitigate the existing need for healthy confectionery, based on the physical-chemical and sensory evaluation of a gummy candy type Parchita pulp base sweetened with stevia. The methodology consisted in the application of a 3² factorial design for the combination of gelatin and agar-agar, also using parchite pulp, corn starch and stevia liquid sweetener, established through a “focus group”, and then through tests Affective and using a semi-trained panel, the combination of stevia with other non-caloric sweeteners such as aspartame and sucralose was evaluated, as well as the use of rebaudioside A, this in order to attenuate the stevia aftertaste. These evaluations allowed reducing the number of samples to the three best treatments, treatment 2 using only stevia as a sweetener, treatment 3 with 3g stevia and 0.5g sucralose and treatment 4 with 3g stevia and 0.6g sucralose ; These formulations were subjected to a physical-chemical evaluation to determine titratable acidity, pH, a_w, total soluble solids, humidity, color and texture. They were analyzed by a panel of consumers made up of 100 children aged between 9 and 12 years, where color, texture, sweetness and global acceptability were evaluated, being treatment 4 (6g jelly, 1g agar-agar, 3g stevia and 0.6gsucralosa) the highest level of pleasure.